Dynamic Analysis On Export, FDI and Growth in Indonesia: An Autoregressive Distributed Lag (ARDL) Model - Mahrus Lutfi Adi Kurniawan; Indanazulfa Qurrota A'yun (Universitas Hayam Wuruk Perbanas, 2021)
This study aims to test the export-led-growth (ELG) hypothesis in Indonesia after the implementation of trade liberalization and analyze the relevance of policies that can be taken by the government. The data used in this study is time series data from 1970- 2020. The analysis method of this research uses the Autoregressive Distributed LagÂ (ARDL) model by applying three models. Model 1 shows that in the short term the ELG hypothesis is proven valid but in the long term the ELG hypothesis is invalid in Indonesia. This is reinforced in model 2 in both of short and long term that real GDP is insignificant to real exports. In the long term, model 2 shows that real exports have a positive effect on FDI and vice versa in model 3 that real GDP has no effect on FDI. The implementation of the results illustrates to policy makers that strong economic growth can attract export capabilities in Indonesia, but policies that are based on economic growth have vulnerabilities to global dynamics that can affect export activities and the investment climate in Indonesia, so export market diversification policies need to be implemented to be able to reach a wider market. From the investment side, it is necessary to carry out structural reforms (such as policies, financial systems, and infrastructure development) so that there is certainty forÂ foreign investors to invest in Indonesia.